Beberapa Catatan Mengenai UU Pengadilan Anak (UU No. 3 ,Tahun 1997) - l moeljatno (Fakultas Hukum Universitas Islam Indonesia, 2004)
This writing describessome normative notes in the act No. 3, 1997 on the Child Court. One of them Is how the role of society guidance can be basic of consideration on judge decision about naughty child. How is theright of child guaranteed during their Court and how is the child not traumatically treatment so, his'personality and soui can be able to growwell up.